KESETARAAN JENDER DALAM POLITIK - Mahfudz - Junaedi (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2019)
Gender equality in politics is one that has so far discussed in Muslim societies and applied in various ways by the Muslim community. There are many interpretations of the verses related to gender can be regarded as a gender biased interpretation, either by the scholars in the long term as well as in modern times. Associated with verses which are often used as a basis for answering whether the woman's equality with men in participating in the field of public leadership and the right to become a leader, some commentators are stuck in a kind of interpretation of gender bias. The Qur'an actually provides flexibility and equal rights to women to participate in politics. It can be concluded that not a single verse in the Qu’ran forbids women to become leaders of the public and that the Qur’an did not distinguish the ability of women in public leadership/politics.